ATTENUATION IN GAS-CHARGED MAGMA - Collier L.; Neuberg J.W.; Lensky N.; Lyakhovsky V.; Navon O. (My University, 2006)
Low frequency seismic events observed on volcanoes, such as Soufriere Hills Volcano, Montserrat, are thought to be caused by a resonating system. The modelling of seismic waves in gas-charged magma is critical for the understanding of seismic resonance effects in conduits, dykes and cracks. Seismic attenuation, which depends mainly on magma viscosity, gas and crystal content, is an essential factor in such modelling attempts. So far only two-phase gas-melt systems with the assumption of no diffusion and transport of volatiles between the melt and the gas bubbles have been considered. In this study, we develop a method of quantifying attenuation within gas-charged magma, including the effects of diffusion and exsolution of gas into the bubbles. The results show that by including such bubble growth processes attenuation levels are increased within magma. The resulting complex behaviour of attenuation with pressure and frequency indicates that two factors are controlling attenuation, the first due to viscous hindrance or the melt, and the second due diffusion processes. The level of attenuation within a gas-charged magma conduit suggests an upper limit on the length of a resonating conduit section of just a few hundred meters. © 2005 Elsevier B.V. All rights reserved.
Keywords: ATTENUATION; BUBBLE GROWTH; LOW FREQUENCY EVENTS; MAGMA; RESONANCE